2016
DOI: 10.1371/journal.pone.0158136
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Dual-Strain Probiotics in Preterm Infants: A Multi-Center Time Series Analysis

Abstract: ObjectiveTo determine the effect of dual-strain probiotics on the development of necrotizing enterocolitis (NEC), mortality and nosocomial bloodstream infections (BSI) in preterm infants in German neonatal intensive care units (NICUs).DesignA multi-center interrupted time series analysis.Setting44 German NICUs with routine use of dual-strain probiotics on neonatal ward level.PatientsPreterm infants documented by NEO-KISS, the German surveillance system for nosocomial infections in preterm infants with birth we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 41 publications
(80 reference statements)
2
46
0
Order By: Relevance
“…Pooled analyses of 4 observational studies [50,51,53,59] showed a statistically significant 51% reduction of NEC and 46% reduction of mortality. Recently, a large observational multicentre study conducted by Denkel et al [71] demonstrated that the routine use of dual-strain probiotics (Infloran) in German neonatal wards significantly reduced the risk of NEC, overall mortality, and late-onset sepsis. These effects were even more pronounced in the subgroup analysis of preterm infants with birth weights below 1,000 g. In the meta-analysis of RCTs where a combination of more than 2 probiotics was used, a statistically significant effect in preventing NEC and mortality was seen.…”
Section: Discussionmentioning
confidence: 99%
“…Pooled analyses of 4 observational studies [50,51,53,59] showed a statistically significant 51% reduction of NEC and 46% reduction of mortality. Recently, a large observational multicentre study conducted by Denkel et al [71] demonstrated that the routine use of dual-strain probiotics (Infloran) in German neonatal wards significantly reduced the risk of NEC, overall mortality, and late-onset sepsis. These effects were even more pronounced in the subgroup analysis of preterm infants with birth weights below 1,000 g. In the meta-analysis of RCTs where a combination of more than 2 probiotics was used, a statistically significant effect in preventing NEC and mortality was seen.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, putting complicated statistics aside, significant benefits for all outcomes were noted in infants ‘colonised’ with the probiotic (Deshpande et al ., ). Inadequate data on extremely preterm infants: Considering that RCT data is available from ˜2000 extremely preterm infants, and Denkel et al . () have reported data on 4600 extremely preterm infants, quoting inadequate data as the reason for not using probiotics in this (most deserving) population is incorrect. In fact the benefits of routine probiotic supplementation were as dramatic as those in very preterm infants in the report by Denkel et al .…”
Section: Evidence Supporting Benefits Of Probiotics In Preterm Infantsamentioning
confidence: 99%
“…Another recent meta-analysis did not show a significant beneficial effect of probiotics on sepsis in 771 ELBW infants included 3. This demands further studies with adequate power on the use of probiotics in infants born <1000 g. Almost at the same time, we published a multicentre time series analysis supporting the beneficial effects of dual-strain probiotics on NEC, overall-mortality and nosocomial bloodstream infections (BSI) in preterm infants 4. Beyond that, we performed a subgroup analyses with 4683 ELBW infants.…”
mentioning
confidence: 99%